Patient-professional and interprofessional communication barriers in cancer-related fatigue management: a monocentric focus-group study among multidisciplinary healthcare professionals : research article - Wagner, Anna S.; Milzer, Marlena; Maatouk, Imad; Wehlen, Lena; Kiermeier, Senta; Steindorf, Karen; Schmidt, Martina (European journal of cancer care, 2025)
Background: Unfavorable patient-professional and interprofessional communication have been identified as barriers to guideline-oriented, effective care of cancer-related fatigue (CRF). Objectives: To illuminate these interactional challenges, this study aimed to explore the perceptions of healthcare professionals (HCPs) regarding (a) handling patients with CRF, (b) challenges in patients’ everyday life, and (c) suggestions to improve CRF management. Methods: Two focus groups were recruited at the University Hospital Würzburg, Germany. Participants were HCPs working with cancer patients in the fields of medicine (n = 4), nursing (n = 3), and psycho-oncology (n = 4). Data were subjected to qualitative content analysis. Results: A circular model was generated, illustrating the potential interaction between HCPs and patients with CRF from the HCP perspective. Concerns of HCPs, such as low self-efficacy in counseling on CRF and feelings of inadequacy through lack of feedback, interplay with patients’ suffering, resulting frustration, and pressure of expectation among others. This complicates empathic exchange, which HCPs actually highlight to meet patients’ needs and realize effective CRF management. To improve CRF management, HCPs suggested implementing standardized operating procedures to clarify responsibilities and to promote interprofessional collaboration in CRF care. Further, they expressed the need for professional training on CRF and on how to communicate with patients in this respect. Additionally, HCPs pointed out the necessity of cultivating reflective practice as HCPs to enhance empathy toward patients presenting CRF. Conclusions: The interprofessional focus-group discussions improved our understanding of the challenges HCPs may perceive in managing CRF, outlined tasks on the institutional level to be addressed in the future, and provided suggestions for immediate adjustments on the individual level. Trial Registration: ClinicalTrials.gov identifier: NCT04921644